Acemetacin cocrystals and salts: structure solution from powder X-ray data and form selection of the piperazine salt - Sanphui, Palash (International Union of Crystallography, 2014)
Acemetacin (ACM) is a non-steroidal anti-inflammatory drug (NSAID), which causes reduced gastric damage compared with indomethacin. However, acemetacin has a tendency to form a less soluble hydrate in the aqueous medium. We noted difficulties in the preparation of cocrystals and salts of acemetacin by mechanochemical methods, because this drug tends to form a hydrate during any kind of solution-based processing. With the objective to discover a solid form of acemetacin that is stable in the aqueous medium, binary adducts were prepared by the melt method to avoid hydration. The coformers/salt formers reported are pyridine carboxamides [nicotinamide (NAM), isonicotinamide (INA), and picolinamide (PAM)], caprolactam (CPR), p-aminobenzoic acid (PABA), and piperazine (PPZ). The structures of an ACM–INA cocrystal and a binary adduct ACM–PABA were solved using single-crystal X-ray diffraction. Other ACM cocrystals, ACM–PAM and ACM–CPR, and the piperazine salt ACM–PPZ were solved from high-resolution powder X-ray diffraction data. The ACM–INA cocrystal is sustained by the acid⋯pyridine heterosynthon and N—H⋯O catemer hydrogen bonds involving the amide group. The acid⋯amide heterosynthon is present in the ACM–PAM cocrystal, while ACM–CPR contains carboxamide dimers of caprolactam along with acid–carbonyl (ACM) hydrogen bonds. The cocrystals ACM–INA, ACM–PAM and ACM–CPR are three-dimensional isostructural. The carboxyl⋯carboxyl synthon in ACM–PABA posed difficulty in assigning the position of the H atom, which may indicate proton disorder. In terms of stability, the salts were found to be relatively stable in pH 7 buffer medium over 24 h, but the cocrystals dissociated to give ACM hydrate during the same time period. The ACM–PPZ salt and ACM–nicotinamide cocrystal dissolve five times faster than the stable hydrate form, whereas the ACM–PABA adduct has 2.5 times faster dissolution rate. The pharmaceutically acceptable piperazine salt of acemetacin exhibits superior stability, faster dissolution rate and is able to overcome the hydration tendency of the reference drug.